Extraction, physicochemical characterisation, and bioactive properties of ink melanin from cuttlefish (Sepiaesculenta). (1st March 2021) - Xie, Jingwen; Li, Hongyan; Che, Hongxia; Dong, Xiufang; Yang, Xihong; Xie, Wancui
Summary: The extracted melanin from Sepia esculenta was characterised by physicochemical properties and biological activities. The yields of melanin were 87.1%, 69.9%, and 62.5% by water extraction, enzymolysis and acidolysis, respectively. The ink melanin contained a characteristic indole structure with irregular spherical structures. Water extraction showed a positive effect on preserving the complete structure of melanin particles based on component analysis, whereas enzymes and acids had destructive effect. Water extraction melanin (WM) exhibited a certain thermal stability and light resistance. WM performed in radical scavenging in a dose‐dependent manner. The IC50 of WM for DPPH and ABTS was 99.8 and 104.2 μg mL −1, respectively. WM protected kojic acid and ascorbic acid from light radiation. As the exposure time to light radiation prolonged, the stability of kojic acid and ascorbic acid was preserved. It indicated that melanin might be potentially used as an antioxidant and photo‐protectant. Abstract : .The process of extraction and characterisation of ink melanin.